# Simplify the given expression below: (6 + 2i) - (8 - 3i)

**Solution:**

Given expression is

(6 + 2i) - (8 - 3i)

The subtraction of complex numbers is performed as follows

The real parts are computed together and then the imaginary parts.

(a+bi) - (c+di) = (a - c) + (bi -di)

=(a-c) + i(b-d)

= (6 - 8) + (2i - (-3i)

= -2 + 2i + 3i

= -2 + 5i

Therefore, the simplified expression is -2 + 5i

## Simplify the given expression below: (6 + 2i) - (8 - 3i)

**Summary:**

The given expression below (6 + 2i) - (8 - 3i) is simplified as -2 + 5i.

Math worksheets and

visual curriculum

visual curriculum